Voyages to Hawaiʻi Before 1860 A Record, Based on Historical Narratives in the Libraries of the Hawaiian Mission Children's Society and The Hawaiian Historical Society, Extended to March 1860 - Judd, Bernice (University of Hawai'i Press, 1974)
No list of voyages to Hawaii has appeared in book form since the interesting group of Hawaiian bibliography was published in the 1860s. It has been worthwhile to reexamine this subject of voyages to Hawaii, although a complete enumeration of the vessels has not been attempted in the present publication. This edition is primarily an enlargement rather than a revised version of Miss Judd's original book.